Estudio, diseño geométrico y estructural de la vía: puente del río Higuerillas – Higuerillas – 12 de octubre – y de Pueblo nuevo, perteneciente a la Parroquia 12 de Diciembre del Cantón Pindal, Provincia de Loja. - Gualán Robles, Hober Augusto (2015)
Higuerillas - - October 12 - The River Bridge Higuerillas track and Pueblo Nuevo is in poor condition, hindering the transfer of local products to market, causing economic losses and hindering the development of the sector and hence growth socio - economic development of its inhabitants; For this reason, this work degree aims to make the geometric and structural design of the road that meets standards M.T.O.P., contributing to its future implementation. Research and inquiry that was conducted was using the method of literature review, consultation on websites, field research and surveying tasks. The traffic count, topography, soil studies and analysis of the asphalt mix, were considered for the geometric design, structural package, Environmental Impact and Costs; for this we adhere to the rules of M.T.O.P. The results obtained are for a design route is of IV Order was designed with a design speed of 50 km / h, has a length of 4.926.23 m., 7.20 m wide., Ditches 0.75m 0.30 wide and deep. It also has two box type culvert pipe and 8 Armico 120 mm in diameter. The structure has a thickness of 7 cm asphalt base 15 cm Class II, Class II sub-base of 15 cm and subgrade improvement of 25 cm.